VARIASI UKURAN DAN TIPE KELOMPOK MUNCAK (Muntiacus muntjak Zimmermann, 1780) BERDASARKAN TIPE VEGETASI DI TAMAN NASIONAL UJUNG KULON - Intannia Ekanasty; Yanto Santosa; U Mamat Rahmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
The size and type of animal groups is affected by various ecological factors, such as vegetation and seasonal changes. Understanding of the environmental factors that influence the variation of size and type of the group is important to manage the species according to its behaviour. This study was conducted by using video trap. There were two types of barking deer group size, solitary (97%) and family unit (3%). Solitary barking deer most frequently recorded in secondary forest, while family unit in shrub vegetation. Six types of group were identified: 46% male groups; 32% female groups; 19% sub adult groups; 3% mixed adult groups; 0.003% adult and sub adult groups; and 0.001% family group. Adult and sub adult groups and family group captured most frequently in shrub, while male, female, and sub adult groups in secondary forest. Mixed adult groups captured most frequently both in shrub and secondary forest. Chi-square test indicated that both group size and group type variation were not correlated with vegetation types. Group types significantly related to the time of survey, but group size was not correlated. Keywords: Barking deer, Group type, Group size, Ujung Kulon National Park, Vegetation types.